2009
DOI: 10.1016/j.joca.2008.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Resistin is elevated following traumatic joint injury and causes matrix degradation and release of inflammatory cytokines from articular cartilage in vitro

Abstract: Resistin is elevated both systemically and locally in the weeks immediately following joint injury and has a direct effect on cartilage matrix turnover and cytokine production. Resistin may play a role in the early stages of trauma-induced OA and may represent a new therapeutic target to slow joint destruction in OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
85
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 39 publications
3
85
1
4
Order By: Relevance
“…Resistin can be detected locally in the synovium of inflamed joints in both rheumatoid arthritis (RA) and OA (Senolt et al 2007;Koskinen et al 2014). Furthermore, resistin increased expression of MMP-1, MMP-13, and ADAMTS-4 in human articular chondrocytes and stimulates proteoglycan degradation, as well as inhibited the production of proteoglycan and type II collagen in mouse and human cartilage explants (Lee et al 2009;Poonpet and Honsawek 2014). In addition, resistin can stimulate inflammatory cytokines, such as IL-6 and TNF-α, as well as PGE 2 synthesis.…”
Section: Discussionmentioning
confidence: 94%
“…Resistin can be detected locally in the synovium of inflamed joints in both rheumatoid arthritis (RA) and OA (Senolt et al 2007;Koskinen et al 2014). Furthermore, resistin increased expression of MMP-1, MMP-13, and ADAMTS-4 in human articular chondrocytes and stimulates proteoglycan degradation, as well as inhibited the production of proteoglycan and type II collagen in mouse and human cartilage explants (Lee et al 2009;Poonpet and Honsawek 2014). In addition, resistin can stimulate inflammatory cytokines, such as IL-6 and TNF-α, as well as PGE 2 synthesis.…”
Section: Discussionmentioning
confidence: 94%
“…Gonzales-Gay et al [35] observed decreased serum resistin level in patients with rheumatoid arthritis after anti-TNF-a therapy. Kaser et al and Lee et al [11,36] found that resistin was elevated both systemically and locally immediately following joint injury and has a direct effect on proinflammatory cytokine production. They suggest that resistin may play a role as an early marker of trauma-induced osteoarthritis.…”
Section: Discussionmentioning
confidence: 98%
“…It can be expected that this increase in a wide range of chemokines will have a significant impact on the cells of cartilage and other related joint tissues and should be considered in the pathophysiology of OA. Recently, we demonstrated that the adipokine, resistin, present in injured joints (12), also increased chemokine genes at both the transcriptional and post-transcriptional levels (13) in temporal patterns similar to the IL-1␤ patterns (6). The post-transcriptional regulation of chemokines was further investigated by us in chondrocytes with resistin (13) and by others in fibroblasts (14).…”
mentioning
confidence: 91%